2001
DOI: 10.1046/j.1540-8175.2001.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Local Wall Thickness Correlate with Pathologic Lesion Size Following Radiofrequency Catheter Ablation: An Intracardiac Echocardiographic Imaging Study

Abstract: Therapeutic RF ablation results in mural swelling and increased echo density. These changes can be detected by ICE imaging and correlate with pathologic lesion size. ICE imaging may be useful in online quantification of lesion size, especially for transmural lesions during clinical catheter ablation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 3 publications
3
40
0
1
Order By: Relevance
“…One is that the tissue surface is altered because of initial RF current, making subsequent ablations more difficult to penetrate deep in the tissue. 16 A more plausible explanation is that creation of a nontransmural lesion results in edema. It has been reported that heart wall thickness can double after 1 minute of ablation because of tissue edema formation.…”
Section: Cf Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that the tissue surface is altered because of initial RF current, making subsequent ablations more difficult to penetrate deep in the tissue. 16 A more plausible explanation is that creation of a nontransmural lesion results in edema. It has been reported that heart wall thickness can double after 1 minute of ablation because of tissue edema formation.…”
Section: Cf Parametersmentioning
confidence: 99%
“…It has been reported that heart wall thickness can double after 1 minute of ablation because of tissue edema formation. 16 Hence, a nontransmural first lesion may increase wall thickness, reducing the effect of tissue heating and making it difficult to achieve full transmurality with subsequent ablations. Therefore, the goal of any RF ablation should be to achieve transmurality with the first attempt.…”
Section: Cf Parametersmentioning
confidence: 99%
“…We have found this most useful in the ventricle, where the wall thickness allows for distinct identification of lesion formation and ablation efficacy. This has been validated in a dog model of healed infarction, with the appearance of significant echogenicity and swelling with effective lesions [20,21]. The appearance of microbubbles at the tissue surface may indicate superheating and allow the operator to decrease or discontinue power delivery and avoid steam pops [22••].…”
Section: Complicationsmentioning
confidence: 99%
“…ICE can also confirm good contact between the ablation electrode and the endocardium during ablation, which allows for optimal energy transfer [18], Lesion formation can be manifest by increased echogenicity and mural thickening [19]. On the other hand, overzealous ablation can cause excessive tissue heating, leading to intramyocardial steam formation and abrupt liberation (steam-pop).…”
Section: Ablation Catheter Contact and Lesion Formationmentioning
confidence: 99%